Heritage Tourism Development Strategy with a Wellness Concept for Old Town Post-Covid-19: A Case Study of Tangerang Old Town (International Journal of Architecture and Urbanism, 2025)
Over the past decade, the revitalization of historical urban areas such as Yogyakarta, Jakarta, and Semarang has inspired other cities in Indonesia to undertake similar projects. However, this trend often leads to a repetition of concepts that may dilute the unique identity of these places. In the aftermath of the Covid-19 pandemic, it is essential to redesign these old city areas while incorporating health protocols. Wellness tourism, a new concept in the tourism sector, presents an alternative approach to revitalize old cities post-pandemic. This concept aligns well with the "friendly city" idea, focusing on both health and community engagement. This study focuses on Tangerang Old Town, which experienced a decline in tourism due to the Covid-19 restrictions. The concept of wellness and heritage tourism draws on local strengths, especially in heritage and wellness sectors. Through a descriptive approach, the study identifies the tourism potential of Tangerang Old Town. The research then evaluates the application of wellness-heritage tourism using the Importance Performance Analysis (IPA) method, based on five key criteria and their respective indicators. The IPA method reveals the priority areas for developing tourism in Tangerang Old Town. The findings suggest that Tangerang Old Town possesses ample potential for development. Key local assets, such as traditional medicine, healing places, and cultural practices, should be rebranded and integrated into tourism strategies. Improvements in infrastructure and facilities, particularly outdoor spaces, dining areas, and gathering spots, are crucial. Enhancing green spaces, providing handwashing stations, trash bins, and ensuring proper distancing in seating arrangements are necessary to comply with health protocols. By adapting to these new requirements, Tangerang Old Town can highlight its distinctive identity and become a safer, more attractive destination for tourism. The wellness heritage tourism concept is particularly suited to create an environmentally friendly city, focusing on sustainable outdoor spaces, social participation, and health services.